Towards semantic user query: A review - Hui-Hui, Wang; Yin-Chai, Wang; Soo-See, Chai (Science Publications, 2015)
This paper attempts to discuss the image query mechanisms and user needs for image retrieval. The explosive growth of image data leads to the need of research and development of Image retrieval. Image retrieval researches are moving from keyword, to low level features and to semantic features. Drive towards semantic features is due to the problem of the keywords which can be very subjective and time consuming while low level features cannot always describe high level concepts in the users’ mind. This paper also highlights both the already addressed and outstanding issues.